Effect of Surface Cleaning and Heat Treatment on Shear Bond Strength of Cement-Contaminated Zirconia - Suwannachot, Laksika; Thamrongananskul, Niyom; Yamockul, Suparaksa; Surintanasarn, Atikom (European Journal of Dentistry, 2025)
This study aimed to evaluate the shear bond strength (SBS) of zirconia to dual-cured resin cement following various cleaning protocols and surface treatments after cement contamination.Seventy-seven zirconia specimens (5 × 5 × 2.5 mm3) were fabricated, polished, and randomly divided into seven groups (n = 11). Ten specimens per group were tested for SBS, and one was reserved for scanning electron microscopy. Group C− was cemented without surface treatment, while group C+ received air abrasion prior to cementation. Groups F − , F + , FT + , S − , and S+ were initially air-abraded and then contaminated with resin cement. F-series groups were cleaned using a furnace, and S-series with a piezoelectric scaler. Among these, F + , FT + , and S+ received additional air abrasion prior to re-cementation, whereas F− and S− did not. Groups F+ and S+ were re-cemented immediately, whereas FT+ was re-cemented 7 days after surface re-treatment. All specimens were artificially aged before SBS testing.One-way ANOVA followed by Tukey's HSD post-hoc test was used for statistical analysis (α = 0.05).Statistically significant differences in SBS were found among the groups (p < 0.05). Group F+ demonstrated the highest bond strength (6.60 ± 1.10 MPa), followed by groups C+ (6.59 ± 0.94 MPa) and S+ (5.42 ± 0.87 MPa), with no significant differences among these three. The lowest SBS was observed in group C− (2.66 ± 0.51 MPa). Intermediate values were recorded in groups F− (4.17 ± 0.95 MPa), FT+ (4.41 ± 0.95 MPa), and S− (4.60 ± 1.17 MPa), which did not differ significantly from each other.Cleaning cement-contaminated zirconia using a furnace or piezoelectric scaler, followed by air abrasion and immediate re-cementation, significantly improves SBS to levels comparable with clean, air-abraded zirconia. Air abrasion enhances bonding efficacy, while delayed re-cementation may diminish bond strength even after surface re-treatment.
Keywords: re-cementation; resin cement; contamination; shear bond strength; surface treatment; zirconia